2018
DOI: 10.1002/humu.23431
|View full text |Cite
|
Sign up to set email alerts
|

MERTK mutation update in inherited retinal diseases

Abstract: MER tyrosine kinase (MERTK) encodes a surface receptor localized at the apical membrane of the retinal pigment epithelium. It plays a critical role in photoreceptor outer segment internalization prior to phagocytosis. Mutations in MERTK have been associated with severe autosomal recessive retinal dystrophies in the RCS rat and in humans. We present here a comprehensive review of all reported MERTK disease causing variants with the associated phenotype. In addition, we provide further data and insights of a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 81 publications
1
49
0
Order By: Relevance
“…Among the other inhibitor targets identified in this screen, mutations affecting MERTK have also been associated with inherited retinopathies, and defects in retinal phagocytosis (57). Furthermore, expression of MERTK is affected in retinal cells of patients with ciliopathies, although no role for MERTK has as yet been defined in maturation of the retinal pigment epithelium in these patients (58).…”
Section: Discussionmentioning
confidence: 99%
“…Among the other inhibitor targets identified in this screen, mutations affecting MERTK have also been associated with inherited retinopathies, and defects in retinal phagocytosis (57). Furthermore, expression of MERTK is affected in retinal cells of patients with ciliopathies, although no role for MERTK has as yet been defined in maturation of the retinal pigment epithelium in these patients (58).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of phagocytosis in central nervous system diseases is, however, less explored. Mutations in MERTK lead to retinal diseases possibly linked to deficient phagocytosis of photoreceptors (130). Similarly, mutations in TREM2 or its bridge protein DAP12 are well known to cause defects in phagocytosis by osteoclasts, causing bone cysts and early dementia (Nasu-Hakola disease) (131).…”
Section: Lesson 10 Does Phagocytosis Execute Cell Death?mentioning
confidence: 99%
“…However, as both ␣V␤5 integrin and CD36 localize at the RPE soma (10,12), their participation in COS recognition and binding is unlikely. A recent large-cohort genetic study of inherited retina diseases found that MerTK mutations exist in a small percentage of CRD patients (40), suggesting a conserved MerTK-dependent mechanism between ROS and COS phagocytosis. In agreement with this, MerTK is expressed at apical RPE microvilli (38).…”
Section: Rab28 and Cone Dystrophymentioning
confidence: 99%